Pharmaceutical process development : current chemical and engineering challenges - Blacker, A. John; Williams, Mike T. (RSC Pub., 2011)
Pharmaceutical process R & D is an exacting, multidisciplinary effort but a somewhat neglected discipline in the chemical curriculum. This book presents an overview of the many facets of process development and how recent advances in synthetic organic chemistry, process technology and chemical engineering have impacted on the manufacture of pharmaceuticals. In 15 concise chapters the book covers such diverse subjects as route selection and economics, the interface with medicinal chemistry, the impact of green chemistry, safety, the crucial role of physical organic measurements in gaining a deepe.
Keywords: Drug development.; Pharmaceutical chemistry.; Pharmaceutical technology.; Drugs -- Design.; elektronické knihy; electronic books